Metaphors in Frank Ocean's Pink+White lyrics - Almas Rifqi Darmawan (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2023)
Song lyrics are one of the linguistic media to analyze since it contains so many analysis possibilities in it and one of them is metaphor. This study is aimed to analyze the lyrics from a song by Frank Ocean entitled Pink + White by using Lakoff and Johnson's metaphors analysis method. The purposes of the study are (1) to describe the metaphors contained in the lyrics and (2) to determine the function of them. A descriptive qualitative method was used in this research to find metaphors in the lyrics. This research explores the use of Lakoff and Johnson’s source and target domain theory in analyzing the lyrics, and how the semantics approach helps to find the function of each metaphor found in the lyrics. The conclusion from this research is the lyrics employed metaphors along with the conceptual metaphor in it and several functions occurred along with the metaphor to help the listeners understand the meaning.